2015
DOI: 10.1002/srin.201400501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stirring Practice on Sulphur and Nitrogen Refining as well as Inclusion Removal in Ladle Treatment

Abstract: The effect of different stirring conditions during ladle treatment on the steel cleanliness was studied in the steel plant of SSAB Special Steels in Oxelösund, Sweden. The cleanliness was examined with regards to the contents of sulfur, nitrogen, and large inclusion (>10 mm). The results showed that vacuum degassing increased the amount of inclusions larger than 10 mm and that subsequent induction stirring suggested a possible positive effect on the inclusion removal. A shortening of the vacuum degassing time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…During the VD process, argon gas is injected into the melt to stir and the open eye of the top slag exposes the molten steel to the high-vacuum atmosphere, enhancing the removal of nitrogen and hydrogen from the melt, as well as inclusions. The removal of inclusions, [9][10][11][12][13][14][15] sulfur, [13,[15][16][17][18] nitrogen, [15,18,19] hydrogen, [18][19][20][21] from the molten steel and the interaction among slag, steel, and inclusions [22,23] during the VD process have been widely investigated through industrial trials and numerical simulations. It was reported that the removal of hydrogen and nitrogen from the molten steel was almost completed within 10 min, while the desulfurization required a longer time during the VD process of tool steels.…”
Section: Introductionmentioning
confidence: 99%
“…During the VD process, argon gas is injected into the melt to stir and the open eye of the top slag exposes the molten steel to the high-vacuum atmosphere, enhancing the removal of nitrogen and hydrogen from the melt, as well as inclusions. The removal of inclusions, [9][10][11][12][13][14][15] sulfur, [13,[15][16][17][18] nitrogen, [15,18,19] hydrogen, [18][19][20][21] from the molten steel and the interaction among slag, steel, and inclusions [22,23] during the VD process have been widely investigated through industrial trials and numerical simulations. It was reported that the removal of hydrogen and nitrogen from the molten steel was almost completed within 10 min, while the desulfurization required a longer time during the VD process of tool steels.…”
Section: Introductionmentioning
confidence: 99%
“…Since then our group has carried out many studies focusing on determining how the inclusion characteristics vary during ladle treatment, based on plant trials [2][3][4][5][6]. Plant trials have also been made to study the following aspects of ladle refining operations: i) the effect of deoxidation praxis and ferroalloy additions on the inclusion characteristics [7][8][9], ii) the influence of the slag on the inclusion characteristics and sulphur content [10][11][12][13], iii) the influence of stirring on the inclusion characteristics [14][15][16][17] and the influence of sampling on determining the inclusion characteristics in process samples [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…(i) the effect of deoxidation praxis and ferroalloy additions on the inclusion characteristics, 20-22 (ii) the influence of the slag on the inclusion characteristics and sulphur content, [23][24][25][26] (iii) the influence of stirring on the inclusion characteristics [27][28][29][30] and the influence of sampling on determining the inclusion characteristics in process samples. [31][32][33] The current study has been made at Uddeholms AB and is mainly focusing on the production route and its properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation